2009
DOI: 10.1080/13218710802620448
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Examination of Sexual Assault Complainants: A Developmental Comparison

Abstract: In light of recent research calling into question the way in which child complainants of sexual assault are cross-examined, the purpose of the present study was to use court transcripts to investigate the questions asked during cross-examination, and the responses given, as a function of whether the complainant was a child or an adult. Although cross-examining lawyers appeared to make some concessions for children, they asked complainants in both age groups a high proportion of very challenging questions. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 61 publications
8
106
4
Order By: Relevance
“…A series of New Zealand studies has examined the way child witnesses were questioned by lawyers (Zajac & Cannan, 2009;Zajac, Gross, & Hayne, 2003) 1 or by forensic interviewers 2 and lawyers (Davies & Seymour, 1998). 3 While these studies, like the present one, were based on nonrepresentative samples, they all reported that children were often asked age-inappropriate questions, particularly in the courtroom.…”
Section: The Present Studymentioning
confidence: 96%
“…A series of New Zealand studies has examined the way child witnesses were questioned by lawyers (Zajac & Cannan, 2009;Zajac, Gross, & Hayne, 2003) 1 or by forensic interviewers 2 and lawyers (Davies & Seymour, 1998). 3 While these studies, like the present one, were based on nonrepresentative samples, they all reported that children were often asked age-inappropriate questions, particularly in the courtroom.…”
Section: The Present Studymentioning
confidence: 96%
“…A few studies have criticized this type of ambiguity in courtroom questioning (Zajac et al, 2003; Zajac & Cannan, 2009), also known as “backward referencing” (Brennan, 1995; Kranat & Westcott, 1994), but the research has predominantly focused on documenting the frequency of potentially ambiguous questions, rather than how well children answer such questions. Zajac and Cannan (2009) were the first to consider children’s responses, but grouped ambiguous questions with a diverse range of questions they termed “complex,” making it difficult to determine if these questions in particular caused children difficulty. Future work can take into account the linguistic developmental work on children’s understanding of anaphora (e.g., Wigglesworth, 1990), as well as expand the range of linguistic devices that are likely to lead to ambiguity (e.g., ellipsis; Lyon, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This is because they often change answers in response to cross-examination -both their correct and their incorrect direct examination answers (Zajac & Hayne, 2003;Zajac, Jury, & O'Neill, 2009). In fact, preschoolers, older children and adults are vulnerable to the deleterious impact of crossexamination (Zajac & Hayne, 2006;Zajac & Cannan, 2009) -highlighting the fact that social pressures can undermine accurate memory reporting. Providing support persons for child witnesses and preparation for legal participation are procedures meant to alleviate some of the stresses of testifying for children and seem to offer some benefits (Malloy et al, 2007).…”
Section: Communication and Linguistic Abilitymentioning
confidence: 99%